M2* - mobility to anywhere, an IoT aggregation service platform - Ferreira, J. C. (2019)
This work addresses the problem of the creation of a central integrated platform to collect and manipulate mobility data and sensor data towards the creation of useful information for users in their mobility process. This is an academic work towards a framework for mobility process, where that manipulate can create useful information for users, public transportation operators and authorities, energy and water real time consumption.